Lutzomyia longipalpis behavior and control at an urban visceral leishmaniasis focus in Argentina - Santini, María Soledad (2010)
Fil: Santini, María Soledad. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.